Prevalence of Tuberculosis Patients Treated in Ba’qhuba Primary Health Care Centers (PHCCs) - Qader Salman , Marwah; Kamal Hameed, Nameer; Faisal Mahmood , Hiba; Khalid Abdullah , Mazin (Diyala Journal of Medicine, 2023)
Background: Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis, is the leading cause of death worldwide. It can be both prevented and treated. There are two types of tuberculosis (pulmonary TB and extrapulmonary TB). Objective: To describe the prevalence of TB cases in PHCCs that covers health services in Ba’qhuba second health sector. Patients and Methods: A cross sectional study was conducted in Ba’qhuba second health sector by using Data of all patients (61 cases) registered in the tuberculosis unit from 1st of Jan 2021 to 1st of Jan 2023, regarding their prevalence and relapse status. The data has been analyzed using Microsoft Excel version 2019. Results: The findings revealed 57% of patients lived in urban areas, the gender ratio was 1:2 male to female, and 26% of cases were among the 45–54 age group. The Incidence of the disease during the two years was 16.1 cases per 100,000 persons while the prevalence was 18.2 cases per 100,000 person-year, TB prevalence regarding the PHHCs was (AL-Yarmouk, Al-Gatton, Bani Saad, and Hay Al-Mustafa) was (5, 4, 2.4, and 0.32 cases per 10,000 person-year, respectively). In terms of TB type, 51% were pulmonary TB (PTB). Regarding EPTB patients 67% had symptoms. According to the sites of infection of EPTB (bones and vertebrae, other, lymph node, pleural effusion, meningitis), they were 33%, 30%, 20%, 13%, and 3%, respectively. And 85% of all patients were in category I of treatment and 15% were in category II due to relapses and 44%of them were laboratory- confirmed and 66% of relapses were pulmonary TB. Conclusion: The prevalence of Al-Yarmouk PHCCs was the highest, almost half of the patients were suffering from Extra-pulmonary TB, while according to relapsed cases pulmonary TB cases were two time more than extra-pulmonary.